Fatigue life prediction of shot peened components - Cláudio,R.A. (2008)
Shot peening is one of the most effective surface treatments in order to prevent crack initiation and early crack propagation. Part of the studies to determine the fatigue performance of shot peening are based on experimental tests. Almost no work is published related with the prediction of shot peening behaviour. The present paper evaluates the ability of the current methodologies, used to predict fatigue life, on components treated with shot peening. The Finite Element Method was used to determine the stress, strain and strain energy due to shot peening of some specimens tested experimentally. These results were used to apply methods to predict the total fatigue life. A final discussion is presented about the ability of the methods used, to predict the fatigue life of the specimens tested experimentally.